Serum leptin level in women with idiopathic intracranial hypertension. Issue 5 (1st May 2002) - Lampl, Y; Eshel, Y; Kessler, A; Fux, A; Gilad, R; Boaz, M; Matas, Z; Sadeh, M
Abstract : Leptin is a protein secreted by adipose cells which influences regulation of energy balance and body weight. Idiopathic intracranial hypertension (IIH) is recognised as a neurological disorder mainly affecting obese females. The aim of this study was to evaluate the association between IIH and serum leptin level in 15 obese patients and compare the results with those for 16 obese and 15 non-obese women. A significantly higher serum leptin level was found in patients with IIH than in controls (p<0.0001), and this did not correlate with body mass index (BMI). Serum leptin levels were significantly associated with BMI in both control groups (p<0.0006). Additional factors must therefore be involved in the phenomenon of serum leptin increase beyond weight gain. The cause can only be hypothesised, but it seems that the origin is central, probably hypothalamic.